IMPACT OF ACCOUNTING INFORMATION SYSTEM IN REDUCING COSTS IN JORDANIAN BANKS - Albashabsheh, Aisar Ayed Nahar; Alhroob, Modafar Nayel; Irbihat, Belal Eid; Javed, Sarfaraz (International Journal of Research -GRANTHAALAYAH, 2018)
This study is an attempt to analyses the impact of accounting information system in reducing costs in Jordanian banks. This study consist primary and secondary method of collecting and analysis data. This study focus on the two main objectives and three hypothesis developed on the after the in-depth study of relevant literature. The need for accounting systems increases in its regard as a mean which derives its importance and necessity from its level of contribution in improving the value chain of business organizations, it helps in providing the needs from various resources and optimally allocating them under conditions of risk and uncertainty surrounding the business environment. The accounting system is considered as one of the most important information systems that contribute to the rationalization and support of economic decisions which affect the resources and wealth of communities and hence on the welfare of individuals. The accounting system also involves a close relationship with relevant administrative process which involves several tasks and functions; thus, contributing in the improvement of the value chain of business organizations and increasing the level of goal achieving performance. The accounting systems are also used as the basis of evaluating the efforts made in various administrative levels to accomplish tasks and achieve goals.